2020
DOI: 10.1016/j.ensci.2020.100279
|View full text |Cite
|
Sign up to set email alerts
|

Severe lymphopenia after subcutaneous cladribine in a patient with multiple sclerosis: To vaccinate or not?

Abstract: Objective To describe a fatal case of influenza A pneumonia in a patient with severe lymphopenia after receiving subcutaneous cladribine to treat her multiple sclerosis (MS). Methods Case report. Results A 53-year-old woman developed fatal influenza pneumonia associated with grade 4 lymphopenia two months after receiving a total dose of 60mg subcutaneous cladribine. Despite treatment with oseltamivir, her condition deteriorated and the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The second patient died from H1N1 influenza-associated pneumonia, as reported previously. 22 This 53-year-old woman had an EDSS of 8.5 and died 11 weeks after completing her first course of Litak ® . Of note, her TLC was within normal range (1.1 × 10 9 L −1 ) 4 weeks after completing the course, but was then admitted at the beginning of week 11 with pneumonia and grade 4 lymphopenia 22 ; she died shortly after.…”
Section: Resultsmentioning
confidence: 99%
“…The second patient died from H1N1 influenza-associated pneumonia, as reported previously. 22 This 53-year-old woman had an EDSS of 8.5 and died 11 weeks after completing her first course of Litak ® . Of note, her TLC was within normal range (1.1 × 10 9 L −1 ) 4 weeks after completing the course, but was then admitted at the beginning of week 11 with pneumonia and grade 4 lymphopenia 22 ; she died shortly after.…”
Section: Resultsmentioning
confidence: 99%
“…Disease duration from first symptoms until data cut-off was 11.0 years (median; IQR: 8.2, 15.5). The reasons why 21 pwMS received only one course of SClad were as follows: personal choice ( n = 6), difficulties travelling to our centre (1), haematopoietic stem cell transplantation (HSCT) (1), switch to fingolimod (1), planned pregnancy (2), death (1), 18 low TLC prior to planned second treatment course (2), intensive treatment unit (ITU) admission following surgery (1), non-specific health issues (1) and not yet due second treatment course at the cut-off date of our cohort (5). Thus, there were 236 pwMS for further analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of similar note, no studies were found in patients taking cladribine, though a recent fatal case of influenza A associated pneumonia within months of administering subcutaneous cladribine causing critical severe lymphopenia was reported [ 69 ]. This raises a question of how to carefully plan MS treatments in the context of not only the disease itself but also of the risk associated with seasonal flu infections and the necessity to administer appropriate vaccinations before the cladribine course is started.…”
Section: Vaccination Overview In the Context Of Multiple Sclerosismentioning
confidence: 99%